2020
DOI: 10.3390/jfmk5020022
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Plexus Injuries in Sport Medicine: Clinical Evaluation, Diagnostic Approaches, Treatment Options, and Rehabilitative Interventions

Abstract: The brachial plexus represents a complex anatomical structure in the upper limb. This “network” of peripheral nerves permits the rearrangement of motor efferent fibers, coming from different spinal nerves, in several terminal branches directed to upper limb muscles. Moreover, afferent information coming from different cutaneous regions in upper limb are sorted in different spinal nerves through the brachial plexus. Severe brachial plexus injuries are a rare clinical condition in the general population and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 91 publications
(119 reference statements)
0
31
0
Order By: Relevance
“…Brachial plexus injuries (BPI) occur mostly due to tra c road accident. Various treatment approaches have been used in this group of the subjects to restore the performance of the upper limb musculatures depends on level of injury [10]. Those with BPI at C7-T1 miss their wrist exion and extension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brachial plexus injuries (BPI) occur mostly due to tra c road accident. Various treatment approaches have been used in this group of the subjects to restore the performance of the upper limb musculatures depends on level of injury [10]. Those with BPI at C7-T1 miss their wrist exion and extension.…”
Section: Discussionmentioning
confidence: 99%
“…Those with lesion at levels C7-T1 have full range of motion in elbow and shoulder joints. However, the strength of the muscles surrounding these joints markedly reduces compared to normal side [1,6,10]. It has been reported that elbow exion and extension strength decreased by 39% and 75%, respectively.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…1 Traumatic cases, especially those involving cervical roots avulsions, tend to cause severe neurological paralysis and frequently require surgery instead of conservative treatment among brachial plexus injuries. 2 Brachial plexus injuries present with a variety of symptoms due to C5-Th1 nerve injury, but complications of diaphragm paralysis have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are approximately 6 to 8 million sport- and recreation-related injuries documented in Europe [ 1 ] and the United States [ 2 ] each year. Among the vast array of injuries experienced by athletes are tendinopathies [ 3 , 4 ] and injuries to muscles [ 5 ], nerves [ 6 ], bones, ligaments, and cartilage [ 7 ]. Because of the adverse physical, psychological, social, and economic effects of sport injury [ 8 , 9 , 10 ], the prediction, prevention, treatment, and rehabilitation of sport injuries and their sequelae have been subjected to extensive scientific inquiry.…”
Section: Introductionmentioning
confidence: 99%